2017
DOI: 10.3389/fpsyt.2017.00144
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Selectively Targeting the α2C-Adrenoceptor in Cognition, Depression, and Schizophrenia—New Developments and Future Perspective

Abstract: α2A- and α2C-adrenoceptors (ARs) are the primary α2-AR subtypes involved in central nervous system (CNS) function. These receptors are implicated in the pathophysiology of psychiatric illness, particularly those associated with affective, psychotic, and cognitive symptoms. Indeed, non-selective α2-AR blockade is proposed to contribute toward antidepressant (e.g., mirtazapine) and atypical antipsychotic (e.g., clozapine) drug action. Both α2C- and α2A-AR share autoreceptor functions to exert negative feedback c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 245 publications
(378 reference statements)
2
55
0
1
Order By: Relevance
“…Hyperexcitation of the neuronal networks is observed in different pathologies (Bondy, ) including hepatic encephalopathy (Dynnik et al, ), ischemic stroke (Song et al, ; Turovsky, Turovskaya, Gaidin, & Zinchenko, ), and epilepsy (El‐Hassar, Esclapez, & Bernard, ). Taking into consideration that activation of different subtypes of adrenergic receptors changes the ion channels activity and intensity of release of neurotransmitters, it can be suggested that the selective agonists of adrenergic receptors may be used for the treatment of neurodegenerative diseases (Gleeson, Ryan, Griffin, Connor, & Harkin, ; Uys, Shahid, & Harvey, ). Agonists of adrenergic receptors demonstrate neuroprotective efficiency under oxygen–glucose deprivation (Maier, Steinberg, Sun, Zhi, & Maze, ; Turovsky et al, ), in Parkinson's disease (Peterson, Ismond, Chapman, & Flood, ), and epilepsy (Halonen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperexcitation of the neuronal networks is observed in different pathologies (Bondy, ) including hepatic encephalopathy (Dynnik et al, ), ischemic stroke (Song et al, ; Turovsky, Turovskaya, Gaidin, & Zinchenko, ), and epilepsy (El‐Hassar, Esclapez, & Bernard, ). Taking into consideration that activation of different subtypes of adrenergic receptors changes the ion channels activity and intensity of release of neurotransmitters, it can be suggested that the selective agonists of adrenergic receptors may be used for the treatment of neurodegenerative diseases (Gleeson, Ryan, Griffin, Connor, & Harkin, ; Uys, Shahid, & Harvey, ). Agonists of adrenergic receptors demonstrate neuroprotective efficiency under oxygen–glucose deprivation (Maier, Steinberg, Sun, Zhi, & Maze, ; Turovsky et al, ), in Parkinson's disease (Peterson, Ismond, Chapman, & Flood, ), and epilepsy (Halonen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A series of 4-aminoquinolines with different linker lengths (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) shown in Fig.1A were synthesized as described previously [8]. All synthesized compounds were identified by proton nuclear magnetic resonance and mass spectrometry ( Supplementary Information, Fig.…”
Section: The Affinity Of 4-aminoquinolines At α 2 -Arsmentioning
confidence: 99%
“…α 2 -ARs have been gradually recognized as promising antipsychotic therapeutic targets, especially for those associated with affective, psychotic, and cognitive symptoms [2]. α 2A -AR is widely distributed in central nervous system (CNS), accounting for 90% of α 2 -ARs, and is associated with regulation and strengthen of memory, analgesia, sedation, and has an anti-epileptic effect [3]. Thus, the activation of the α 2A -AR can improve the clinic symptoms of CNS degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An inhibitory G-protein coupled receptor of the neurotransmitter noradrenaline (NA), the α2C-adrenoceptor (α2C-AR) subtype, has attracted considerable interest as a therapeutic target to treat CNS disorders (1). The α2C-AR may be involved in mediation of the fine-tuning effects of NA on central neurotransmission, particularly during stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained with gene-targeted (knock-out) mice indicate that manipulation of α2A-AR and α2C-AR activation yields differential behavioural effects in nonclinical tests that are commonly used for assessing antidepressant, antipsychotic or pro-cognitive properties of drugs (1). This has led to the proposition that selective α2C-AR antagonism might be a 3 promising approach for the treatment of neuropsychiatric symptoms, potentially across a wide range of CNS disorders, with an improved therapeutic profile compared to non-selective α2-AR antagonists (1) .…”
Section: Introductionmentioning
confidence: 99%